Dietary curcumin enhances intestinal antioxidant capacity in ducklings via altering gene expression of antioxidant and key detoxification enzymes. (14th March 2019) - Ruan, D; Zhu, Y W; Fouad, A M; Yan, S J; Chen, W; Zhang, Y N; Xia, W G; Wang, S; Jiang, S Q; Yang, L; Zheng, C T
ABSTRACT: The study investigated the effects of dietary curcumin supplementation on tissue distribution of curcumin and its metabolites, intestinal antioxidant capacity, and expression of detoxification-related genes in ducks. A total of 720 one-day-old male Cherry Valley Pekin ducklings (initial BW 58.6 ± 0.1 g) were randomly assigned to 4 dietary groups each with 6 replicates of 30 ducks using a single factorial arrangement design. Ducks in the control group were fed a basal diet and the remainder were fed the basal diet supplemented with 200, 400, or 800 mg/kg curcumin. The experiment lasted for 21 D. Curcumin was present at 13.12 to 16.18 mg/g in the cecal digesta, 75.50 to 575.40 μg/g in jejunal mucosa, 35.10 to 73.65 μg/g in liver, and 7.02 to 7.88 μg/mL in plasma. The jejunal and hepatic contents of curcumin increased significantly ( P < 0.05) in response to supplementation with 400 and 800 mg/kg of curcumin respectively, compared with 200 mg curcumin/kg group. There was a linear ( P < 0.001) effect of dietary curcumin on relative abundance of SOD1, GPX1, CAT, HO-1, and Nrf2 transcripts, and a quadratic ( P < 0.001) increase in the activities of GSH-Px and T-AOC in jejunal mucosa. The expression of CYP1A4, CYP2D17 increased and CYP1B1, CYP2A6 decreased linearly ( P < 0.001) with dietary curcumin concentrations. In addition, dietary curcumin increased gene expression of GST, MRP6, and ABCB1 in jejunal mucosa. In conclusion, dietary supplementation with 200 to 800 mg/kg curcumin enhanced the accumulation of curcumin and its metabolites in jejunum as well as increasing the antioxidant capacity and detoxification potential, which play major roles in the protection of duck intestines against damage.